2012
DOI: 10.1007/s10597-012-9541-y
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Experienced by Paid Peer Providers in Mental Health Recovery: A Qualitative Study

Abstract: Peer providers are increasingly employed in mental health services. We explored challenges experienced by 31 peer providers in diverse settings and roles using in-depth interviews, as part of a larger study focusing on their recovery (Moran et al. in Qual Health Res, 2012). A grounded theory approach revealed three challenge domains: work environment, occupational path, and personal mental health. Challenges in the work environment differed between conventional mental health settings and consumer-run agencies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
184
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(202 citation statements)
references
References 34 publications
10
184
1
7
Order By: Relevance
“…Moran et al (2013) connected such pressures to the tension participants experienced in keeping a balance between their desire to help and their need to take care of themselves: A particularly challenging aspect of the role is the dual identity as both service consumer/user and service provider, which impacts on relationships and boundaries with both professional colleagues and clients. This resonated in all but two (5, 9) studies.…”
Section: Sense Of Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moran et al (2013) connected such pressures to the tension participants experienced in keeping a balance between their desire to help and their need to take care of themselves: A particularly challenging aspect of the role is the dual identity as both service consumer/user and service provider, which impacts on relationships and boundaries with both professional colleagues and clients. This resonated in all but two (5, 9) studies.…”
Section: Sense Of Identitymentioning
confidence: 99%
“…One review paper found that consumer-led mental health services reported client outcomes that were equally positive to those reported by traditional services (Doughty and Tse, 2011). The growth in PSW is of little surprise given it is consistent with both recovery-oriented system transformation processes (Moran et al, 2013) and may also fit with economic agendas due to potential cost-savings (Solomon, 2004). A review of cost-effectiveness found that the financial benefits to services of employing PSWs exceeded the costs (Trachtenberg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…. VPW At times peer workers had to contend with an element of mistrust from the people they sought to support, and these challenges have also been seen in another recent, qualitative exploration of the peer worker role: 83 I know there's people in here that probably wouldn't appreciate having a talk with [the peer worker] because they just see [the peer worker] as another member of staff. PSU Occasionally, even from a person on the ward, I would get negative, like, 'Oh, you're working for the other side now.'…”
Section: Sameness and Differencementioning
confidence: 99%
“…The potential benefits of introducing peer workers can be undermined where expectations of the role are not shared; for example, where peer workers are not given sufficient autonomy to use their lived experience in their role (Moran 2012). Difference in expectation of whether or not peer workers should work to conventional, clinical practice boundaries has been highlighted (Mead 2006), and resistance among existing staff can also be encountered where there are perceived challenges to professional jurisdiction (Currie 2009).…”
Section: Shared Expectations Of the Peer Worker Rolementioning
confidence: 99%
“…Where the introduction of peer workers is specifically linked to organisational delivery on a recovery or social inclusion agenda, for example, there might be greater clarity of expectation around the function of the role. Conversely, peer workers have reported that their role felt undermined where attitudes to individual recovery were not shared by their managers and co-workers (Moran 2012). It has been suggested that strategic alignment has to be established on a number of levels -organisation, team and individual -for it to be effective (Nadler 1980).…”
Section: Strategic Alignmentmentioning
confidence: 99%